Task Cube: A three-dimensional conceptual space of user tasks in visualization design and evaluation. (October 2016) - Rind, Alexander; Aigner, Wolfgang; Wagner, Markus; Miksch, Silvia; Lammarsch, Tim
User tasks play a pivotal role in visualization design and evaluation. However, the term 'task' is used ambiguously within the visualization community. In this article, we critically analyze the relevant literature and systematically compare definitions of 'task' and the usage of related terminology. In doing so, we identify a three-dimensional conceptual space of user tasks in visualization, referred to as the task cube, and the more precise concepts 'objective' and 'action' for tasks. We illustrate the usage of the task cube's dimensions in an objective-driven visualization process, in different scenarios of visualization design and evaluation, and for comparing categorizations of abstract tasks. Thus, visualization researchers can better formulate their contributions which helps advance visualization as a whole.